Bosnia and Herzegovina : Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This report highlights Bosnia and Herzegovina's Request for Stand-By Arrangement (SBA). The authorities have requested a 15-month SBA in the amount of SDR 67.6 million (40 percent of quota) for June 2002-September 2003. Private investment and FDI remain mired in concerns over political risks, the hostile business environment, and infrastructure bottlenecks. Fixed investment outside government, construction, and reconstruction is low-perhaps 10 percent of GDP, and construction is slowing as aid inflows are curtailed. Significant fiscal consolidation appears to have been achieved in 2001 and fiscal structures have been strengthened.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet